Reprogramming somatic cells without fusion or ethical confusion. (November 2006) - Mali, Prashant; Cheng, Linzhao
Evaluation of: Takahashi K, Yamanaka S: Induction of pluripotent stem cells from mouse embryonic and adult fibroblast cultures by defined factors. Cell 126, 663––676 (2006)  [1] . Somatic cell nuclear transfer experiments in the past 10  years demonstrate that mammalian cells can be reprogrammed, since the nucleus of a differentiated somatic cell, when injected into an enucleated oocyte, can, upon transfer to a surrogate mother, give rise to an entire organism. Cell fusion of differentiated cells with mouse and human embryonic stem cells also results in hybrids (although in tetraploids) that have many unique features of pluripotent embryonic stem cells. Furthermore, exposure of somatic cells or nuclei to cell extracts from oocytes or embryonic stem cells can lead to reprogramming to a more multipotent state. While these experiments highlight that nuclear reprogramming is indeed possible through several means, the underlying molecular details and necessary gene expression have not yet been elucidated. In a recent Cell report, Takahashi and Yamanaka take a significant step in this direction. They demonstrate, for the first time, that adult and embryonic mouse fibroblasts can be reprogrammed into embryonic stem cell-like pluripotent cells by the overexpression of four genes. Could this achievement be reproduced in human somatic cells, and if so, how?